Next-generation sequencing of tyrosine kinase inhibitor-resistant non-small-cell lung cancers in patients harboring epidermal growth factor-activating mutations. Issue 1 (December 2015) - Masago, Katsuhiro; Fujita, Shiro; Muraki, Miho; Hata, Akito; Okuda, Chiyuki; Otsuka, Kyoko; Kaji, Reiko; Takeshita, Jumpei; Kato, Ryoji; Katakami, Nobuyuki; Hirata, Yukio
Abstract Background The aim of this study was to detect the epidermal growth factor receptor (EGFR)-activating mutations and other oncogene alterations in patients with non-small-cell lung cancers (NSCLC) who experienced a treatment failure in response to EGFR-tyrosine kinase inhibitors (TKIs) with a next generation sequencer. Methods Fifteen patients with advanced NSCLC previously treated with EGFR-TKIs were examined between August 2005 and October 2014. For each case, new biopsies were performed, followed by DNA sequencing on an Ion Torrent Personal Genome Machine (PGM) system using the Ion AmpliSeq Cancer Hotspot Panel version 2. Results All 15 patients were diagnosed with NSCLC harboringEGFR -activating mutations (seven cases of exon 19 deletion, seven cases of L858R in exon 21, and one case of L861Q in exon 21). Of the 15 cases, acquired T790M resistance mutations were detected in 9 (60.0 %) patients. In addition, other mutations were identified outside ofEGFR, including 13 cases (86.7 %) exhibitingTP53 P72R mutations, 5 cases (33.3 %) ofKDR Q472H, and 2 cases (13.3 %) ofKIT M541L. Conclusions Here, we showed that next-generation sequencing (NGS) is able to detectEGFR T790M mutations in cases not readily diagnosed by other conventional methods. Significant differences in the degree ofEGFR T790M and otherEGFR -activating mutations may be indicative of the heterogeneity of disease phenotype evident within these patients. The co-existence of known oncogenic mutations within each of these patients may play a role in acquired EGFR-TKIs resistance, suggesting the need for alternative treatment strategies, with PCR-based NGS playing an important role in disease diagnosis.